Anglicismos léxicos en espanol y en eslovaco - Ulašin, Bohdan (Verba hispanica, 2015)
This article compares two languages, Castillian Spanish and Slovak and contrasts the status and use of English loanwords in each language. It is a small part of a larger project comparing the lexical and semantic levels of both languages. The article classifies and gives examples of differences in the treatment of anglicisms between the two, starting with phonetic differences (introducing the most notable ones), orthographic, semantic and structural differences, then looking at synonyms and calques and ending with a discussion of the presence or absence of anglicisms in the cases of denotative mismatches. We also emphasize the importance of taking into account the cultural equivalent of the English loanwords in the extralinguistic reality of Spain and Slovakia. The phenomenon of so called pseudo-anglicisms in Spanish is mentioned, as well as the extremely numerous presence of false friends in Spanish (in comparison with Slovak). The article summarises the most typical differences between European Spanish and American Spanish varieties with regard to English loanwords. The article also discusses the case of acronyms, contrasting the use of English international acronyms in Slovak with the tendency to translate them in Spanish.
Keywords: Spanish; španščina; slovaščina; anglicizmi; lažni prijatelji; kalki